1983
DOI: 10.1111/j.1469-7998.1983.tb02089.x
|View full text |Cite
|
Sign up to set email alerts
|

Attachment between Harbour seal (Phoca vitulina) mothers and pups*

Abstract: Behavioural interactions between Harbour seal mothers and pups at Miquelon revealed that the following behaviour of the pup generally ensures that the pair stay together, though the mother takes over this rôle when necessary. This relationship held true when the animals were hauled out on the sandflats, and when they were in the water. Our results imply, contrary to suggestions in the literature, that the pup is able to distinguish its mother from other females. The tendency of the pup to follow its mother is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…The behaviour of the mother and pup during the lactation period seems to vary among common seals in different habitats. On the one hand, there are populations showing a very strong and continuous bond between mother and pup; these include the populations in the Humboldt Bay, California (Knudtson 1975), the Shetlands (Venables and Venables 1955) and New foundland, Canada (Renouf et al 1983). On the other hand, there are other populations in which the mothers leave their pups on the haul out and move out to sea to forage.…”
Section: Mother-pup Bondmentioning
confidence: 98%
“…The behaviour of the mother and pup during the lactation period seems to vary among common seals in different habitats. On the one hand, there are populations showing a very strong and continuous bond between mother and pup; these include the populations in the Humboldt Bay, California (Knudtson 1975), the Shetlands (Venables and Venables 1955) and New foundland, Canada (Renouf et al 1983). On the other hand, there are other populations in which the mothers leave their pups on the haul out and move out to sea to forage.…”
Section: Mother-pup Bondmentioning
confidence: 98%
“…In previous studies of maternal behaviour in Harbour seals (Phoca vitulina), we have elaborated upon the unique difficulties which this pinniped species faces in ensuring that the mother and her offspring stay together from birth until weaning (Renouf & Diemand, In press;Renouf, Lawson et al, 1983). Our work with a breeding colony ofabout 700 Phoca vitulina at Miquelon, a small French department off the South Coast of Newfoundland, indicated that the pups are predisposed at an early age, possibly less than 40 min after birth (Lawson, 1983), to follow their mother's movements analogous to the manner in which precocial avians imprint upon their mothers (Lorenz, 1937).…”
Section: Introductionmentioning
confidence: 99%
“…0022-5460/84/040583 + 08 $03.00/0 583 0 1984 The Zoological Society of London of the relationship. She appears t o monitor the youngster's movements, most obviously so in the water where the pup is more mobile, and very clearly so when the pair have been flushed into the sea by a disturbance (Renouf, Lawson et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance near the time of parturition, when the mother-pup bond is just being established, can cause mother-pup separations that result in permanent abandonment and subesequent starvation of pups (Johnson 1977, Renouf et al 1983, Osinga et al 2012. Disturbances also disrupt nursing and resting times for pups.…”
mentioning
confidence: 99%